Opsi Religius dan Realitas Kemartiran: Konversi Masyarakat Lembata ke Kekatolikan dalam Konteks Misi Awal SVD (1920-1950) - Camnahas, Antonio (Institut Filsafat dan Teknologi Kreatif Ledalero, 2025)
Catholicism in Lembata has been built on the blood of the martyrs. It is also on this basis that SVD missionaries started their work there 100 years ago. The presence of the SVD marks an important momentum for a more serious mission work on this island. Pastor Bernhard Bode, SVD was the first SVD pastor to live there in 1920. With his